2016
DOI: 10.1007/s00261-016-0658-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of strain elastography for differentiation between renal cell carcinoma and transitional cell carcinoma of kidney

Abstract: Strain elastography can be used as a valuable imaging technique for preoperative differentiation between RCC and TCC of kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
10
0
8
Order By: Relevance
“…[7] Basic assumption of SE is that soft tissues can be more deformable than hard ones which can be displayed on US as a colour map overlaid to the grey scale image. [8] The resultant strain ratio (SR) represents the ratio of stiffness of the target and normal tissues. Studies reported that objectively measured tissue stiffness by SE may be used as a diagnostic marker in clinical practice for the differentiation between benign and malignant tissues in various organs.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Basic assumption of SE is that soft tissues can be more deformable than hard ones which can be displayed on US as a colour map overlaid to the grey scale image. [8] The resultant strain ratio (SR) represents the ratio of stiffness of the target and normal tissues. Studies reported that objectively measured tissue stiffness by SE may be used as a diagnostic marker in clinical practice for the differentiation between benign and malignant tissues in various organs.…”
Section: Introductionmentioning
confidence: 99%
“…Görüntüleme alanı renal sinüs ve parankim aynı kesitte olacak şekilde alınır. Böbreğe prob ile aksiyel planda dik olarak kısa aralıklarla ritmik olarak kompresyon ve dekompresyon uygulanır (5). Uygulanan kompresyon ve dekompresyonun süre ve miktar olarak en uygun şekli yazılımsal olarak ekranın sol alt köşesinde gösterilen kompresyon-zaman skalası ile belirlenir.…”
Section: Elastografi Uygulamalarıunclassified
“…Uygulanan kompresyon ve dekompresyonun süre ve miktar olarak en uygun şekli yazılımsal olarak ekranın sol alt köşesinde gösterilen kompresyon-zaman skalası ile belirlenir. Değerlendirilen bölgenin gri-skala ve elastogram verileri ekran üzerinde eş zamanlı olarak yan yana iki ayrı pencerede izlenebilir (5,9). Elde edilen dinamik ve statik görüntüler dijital ortamda kaydedilir.…”
Section: Elastografi Uygulamalarıunclassified
See 2 more Smart Citations